First record of Nelsonia goldmani in the state of Morelos, Mexico - Francisco X. González-Cózatl; Rachel M. Vallejo; Elizabeth Arellano (Revista Mexicana de Biodiversidad)
We report Nelsonia goldmani in the state of Morelos for the first time. This new record constitutes a range extension of the distribution of this species of over 100 km to the southeast of the nearest known localities. The collecting site is located less than 40 km south of Mexico City, within the limits of two natural protected areas that have been surveyed for more than half century. The fact that previous inventories in this region had not registered the occurrence of this Mexican endemic and endangered species, confirms its rareness and the need of further exhaustive surveys to accurately document Mexican biodiversity.